2016
DOI: 10.3889/oamjms.2016.125
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of the Aged Patients at a Large Cardiac Rehabilitation Center in the Southern Brazil and Some Aspects of Their Dropout from the Therapeutic Programs

Abstract: AIM:This paper aims to assess the dropout rate in different age groups through the example of the large cardiac rehabilitation centre affiliated with the Institute of Sports Medicine, University of Caxias do Sul.MATERIAL AND METHODS:A historic cohort study comprising the following groups: Non-Old < 65 (n = 141); Young-Old 65-74 (n = 128); and Middle-Old 75-84 years old (n = 57). The exercise program lasted 48 sessions and dropout was defined as attendance of 50% of sessions or less. Logistic binominal regressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
1
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 36 publications
1
1
1
1
Order By: Relevance
“…In addition, 10 patients (7.2%) completed primary education, 50 patients (36.0%) completed secondary education, 61 patients (43.9%) completed tertiary education, and 18 patients (12.9%) did not indicate their education level. The dropout rate of 28.4% is consistent with a similar study that was done in the United Kingdom [ 26 ], and is lower than a recent study done in Brazil [ 27 ].…”
Section: Methodssupporting
confidence: 90%
“…In addition, 10 patients (7.2%) completed primary education, 50 patients (36.0%) completed secondary education, 61 patients (43.9%) completed tertiary education, and 18 patients (12.9%) did not indicate their education level. The dropout rate of 28.4% is consistent with a similar study that was done in the United Kingdom [ 26 ], and is lower than a recent study done in Brazil [ 27 ].…”
Section: Methodssupporting
confidence: 90%
“…Our results demonstrated high discontinuation rates, in which 74% of the participants discontinued after a median length of permanence equal to 10.8 months. This discontinuation rate is much higher than that found in other studies for CRP [26,27], although another study described rates of 82% in middle‐income countries [28]. These conflicting results can be attributed to differences in the severity of heart disease and cardiac function between study populations, in which 76.2% of our patients presented HF, with low LVEF (33.0% ± 9.3%) and low functional class (NYHA III–IV; 59.5%), representing a very severe disease.…”
Section: Discussioncontrasting
confidence: 64%
“…With respect to age, our data differ from a recent study that demonstrated that adherence in elderly patients is lower than in younger patients. 41 Demographic and clinical features, as well as different SEP may explain the discrepancy in these results.…”
Section: Discussionmentioning
confidence: 93%